Bactericidal activity of single dose of clarithromycin plus minocycline, with or without ofloxacin, against Mycobacterium leprae in patients. - Ji, B (1996)
Fifty patients with newly diagnosed lepromatous leprosy were allocated randomly to one of five groups and treated with either a month-long standard regimen of multidrug therapy (MDT) for multibacillary leprosy, a single dose of 600 mg of rifampin, a month-long regimen with the dapsone (DDS) and clofazimine (CLO) components of the standard MDT, or a single dose of 2,000 mg of clarithromycin (CLARI) plus 200 mg of minocycline (MINO), with or without the addition of 800 mg of ofloxacin (OFLO). At the end of 1 month, clinical improvement accompanied by significant decreases of morphological indexes in skin smears was observed in about half of the patients of each group. A significant bactericidal effect was demonstrated in the great majority of patients in all five groups by inoculating the footpads of mice with organisms recovered from biopsy samples obtained before and after treatment. Rifampin proved to be a bactericidal drug against Mycobacterium leprae more potent than any combination of the other drugs. A single dose of CLARI-MINO, with or without OFLO, displayed a degree of bactericidal activity similar to that of a regimen daily of doses of DDS-CLO for 1 month, suggesting that it may be possible to replace the DDS and CLO components of the MDT with a monthly dose of CLARI-MINO, with or without OFLO. However, gastrointestinal adverse events were quite frequent among patients treated with CLARI-MINO, with or without OFLO, and may be attributed to the higher dosage of CLARI or MINO or to the combination of CLARI-MINO plus OFLO. In future trials, therefore, we propose to reduce the dosages of the drugs to 1,000 mg of CLARI, 100 mg of MINO, and 400 mg of OFLO.